2017
DOI: 10.1016/j.ssmph.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A couple-level analysis of participation in physical activity during unemployment

Abstract: There is a well-documented negative correlation between unemployment and health. Yet, little research has examined how unemployment relates to participation in physical activity, and few researchers have considered how an individual's unemployment may affect the health of their spouse or partner. The purpose of this study is to answer three questions: 1. Is one's own unemployment associated with changes in physical activity participation? 2. Is one's partner's unemployment associated with changes in physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
5
13
1
Order By: Relevance
“…For men, total time in exercise does not vary by partner's unemployed/OOLF status, but women with nonworking partners exercise slightly less. This is consistent with recent research (Gough, 2017) and may reflect differential labor market responses to a partner's unemployment/OOLF status. Men's partners are more likely to be voluntarily OOLF, and men tend to work full time, so they may not increase paid labor time if their partner stops working.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For men, total time in exercise does not vary by partner's unemployed/OOLF status, but women with nonworking partners exercise slightly less. This is consistent with recent research (Gough, 2017) and may reflect differential labor market responses to a partner's unemployment/OOLF status. Men's partners are more likely to be voluntarily OOLF, and men tend to work full time, so they may not increase paid labor time if their partner stops working.…”
Section: Discussionsupporting
confidence: 92%
“…Unemployed and OOLF men spend more time exercising overall, alone, and with others compared to employed men, contrary to H1. These results conflict with research that indicated men do not change their exercise during unemployment (Gough, 2017). The current study is cross-sectional, so unobserved time-invariant characteristics may explain some of this conflict.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The latter two may additionally fuel the duration of the unemployment in a vicious cycle. Several studies further observed a decrease in the amount of physical activity in unemployed compared to employed persons [9,10] This lack of health-enhancing physical activity may further worsen the vicious cycle. In such a vicious cycle of reduced work ability, increased stress levels, and lower physical activity exists, specific stress-reducing work-ability-enhancing or physical-activity-promoting programs may be able to counteract against this process.…”
Section: Introductionmentioning
confidence: 99%